2000
DOI: 10.1128/jvi.74.22.10838-10845.2000
|View full text |Cite
|
Sign up to set email alerts
|

Latent Membrane Protein 2A-Mediated Effects on the Phosphatidylinositol 3-Kinase/Akt Pathway

Abstract: Epstein-Barr virus (EBV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 68 publications
(62 reference statements)
6
136
0
1
Order By: Relevance
“…LMP2A and bovine leukemia virus gp 30 were first shown to issue ITAM-dependent signals in T cells (Beaufils et al, 1993). Some functions of the ITAM-containing viral proteins may relate to tumorigenicity, such as survival signalling by activation of the PI3K-Akt pathway by LMP2A and KSHV K1 (Scholle et al, 2000;Swart et al, 2000;Tomlinson and Damania, 2004) and stimulation of cellular migration and invasiveness by LMP2A and MMTV env (Katz et al, 2005;Lu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LMP2A and bovine leukemia virus gp 30 were first shown to issue ITAM-dependent signals in T cells (Beaufils et al, 1993). Some functions of the ITAM-containing viral proteins may relate to tumorigenicity, such as survival signalling by activation of the PI3K-Akt pathway by LMP2A and KSHV K1 (Scholle et al, 2000;Swart et al, 2000;Tomlinson and Damania, 2004) and stimulation of cellular migration and invasiveness by LMP2A and MMTV env (Katz et al, 2005;Lu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine residues involved in Shb binding to LMP2A control constitutive Akt activation The LMP2A ITAM tyrosines Y74 and Y85 were previously shown to bind the Syk tyrosine kinase (Longnecker et al, 1991) and mutations of these tyrosines were shown to influence Syk binding to LMP2A as well as LMP2A-mediated Akt activation and survival signalling (Scholle et al, 2000;Swart et al, 2000). Here, we confirm the negative effect of the Y74F and Y85F mutations on the ability of LMP2A to activate Akt (Figure 6, lanes 11 and 12) and extend this observation by showing that the Y64F mutation suppresses Akt activation by LMP2A, either alone (lanes 5 and 6) or in combination with the Y74F mutation (lanes 9 and 10).…”
Section: Downregulation Of Shb Impairs Lmp2a-mediated Akt Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins include EpsteinBarr virus (EBV) LMP2A, murine mammary tumor virus (MMTV) Env, and Kaposi's sarcoma-associated herpesvirus (KSHV) K1 (Caldwell et al, 1998;Lee et al, 1998a;Katz et al, 2005). Studies of signaling by LMP2A (Longnecker et al, 1991;Caldwell et al, 1998;Swart et al, 2000) and K1 (Lee et al, 1998a;Lagunoff et al, 1999) in B cells suggests that these ITAMs are capable of signaling in a manner similar to traditional cellular ITAMs. Additionally, nonhematopoietic cells expressing K1 and LMP2A are susceptible to transformation and in vivo tumor development (Lee et al, 1998b;Scholle et al, 2000;Prakash et al, 2002).…”
Section: Introductionmentioning
confidence: 99%